PRAKTIKUM MENGUJI KANDUNGAN YANG TERDAPAT PADA BAHAN MAKANAN - Cinta Zahra Dwi Putri Br Purba; Tri Wantini; Nurul Hasanah (Kampus Akademik Publiser, 2025)
This practicum aims to identify the main nutritional contents such as carbohydrates (starch), protein, glucose (simple sugars), and fat in various types of food using simple biochemical testing methods. The activity was conducted by sixth-semester students of the Primary School Teacher Education Study Program (PGSD) at STKIP Al- Maksum Langkat as part of the Science Practicum course. The experimental method used involved testing food samples with Biuret solution for protein, Lugol's iodine for carbohydrates, Benedict's solution for glucose (with heating), and grease spot test using oil paper for fat detection. The observations showed that each food sample contained different types of nutrients. Rice and sweet potatoes were rich in starch, eggs and fish were high in protein and fat, while bananas and corn contained glucose. Vegetables such as spinach and cassava leaves were found to contain fiber, a small amount of protein, and iron. This practicum provided students with direct understanding of nutrient composition in food and emphasized the importance of consuming a balanced and nutritious diet in daily life. In addition, the activity also helped develop students’ science process skills, such as observation, analysis, and interpretation of experimental results.